2018
DOI: 10.1038/s41598-018-27423-z
|View full text |Cite
|
Sign up to set email alerts
|

Screening and characterization of prophages in Desulfovibrio genomes

Abstract: Bacteria of the genus Desulfovibrio belong to the group of Sulphate Reducing Bacteria (SRB). SRB generate significant liabilities in the petroleum industry, mainly due to their ability to microbiologically induce corrosion, biofilm formation and H2S production. Bacteriophages are an alternative control method for SRB, whose information for this group of bacteria however, is scarce. The present study developed a workflow for the identification of complete prophages in Desulfovibrio. Poly-lysogenesis was shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 48 publications
6
21
3
1
Order By: Relevance
“…3 & Table S9), while no virus sequences were detected in the four deltaproteobacterial genome bins. Seven and three viruses were found in D. vulgaris and D. multivorans respectively, which seemed to be not in complete agreement with previous ndings that eight and no viruses were identi ed in the two model SRMs correspondingly [47,61]. This discrepancy likely resulted from the utilization of different viral prediction methods.…”
Section: Viruses Of Srmscontrasting
confidence: 77%
“…3 & Table S9), while no virus sequences were detected in the four deltaproteobacterial genome bins. Seven and three viruses were found in D. vulgaris and D. multivorans respectively, which seemed to be not in complete agreement with previous ndings that eight and no viruses were identi ed in the two model SRMs correspondingly [47,61]. This discrepancy likely resulted from the utilization of different viral prediction methods.…”
Section: Viruses Of Srmscontrasting
confidence: 77%
“…The G4P1-like prophages were common in the genomes of B. vietnamiensis being found in 17% of the strain collection. Although phage genomes are renowned for being mosaic in nature [7], recent studies have used genomics to discover the presence of syntenous prophages across different species [77,78], and across different strains of the same species [79][80][81][82]. The present study is the first to report the population genomics of B. vietnamiensis and map prophage carriage onto the population.…”
Section: Discussionmentioning
confidence: 91%
“…The genus Desulfovibrio, a dominant group of Sulfate Reducing Bacteria (SRB), is a class of anaerobic bacteria which can reduce sulfate to produce H 2 S. Endogenous H 2 S can inhibit the oxidation of acid salts, affect the respiration of cells and induce apoptosis and chronic inflammation. It has been reported that Desulfovibrio is related to the occurrence and development of colon cancer, irritable bowel syndrome, metabolic syndrome and other diseases (Crispim et al, 2018). Hence, Isoflavones are essential in the diet.…”
Section: Discussionmentioning
confidence: 99%